Clinical and Virological Response to Entecavir in HBV-Related Chronic Hepatitis or Cirrhosis: Data from the Clinical Practice in a Single-Centre Cohort. Issue 1 (January 2013) - Marengo, Andrea; Bitetto, Davide; D'Avolio, Antonio; Ciancio, Alessia; Fabris, Carlo; Marietti, Milena; Toniutto, Pierluigi; Perri, Giovanni Di; Rizzetto, Mario; Marzano, Alfredo
Background: Limited data are available on entecavir in Caucasian patients with HBV cirrhosis or chronic hepatitis B who are treated in the clinical practice. The aim was to evaluate the efficacy of entecavir in an Italian cohort of unselected patients with different stages of liver fibrosis, comparing the virological and clinical results obtained between patients with and without liver cirrhosis. Methods: Efficacy and safety of entecavir were retrospectively evaluated in 100 patients recruited in the Gastro-Hepatology Unit, San Giovanni Battista Hospital (Turin, Italy). A pharmacokinetic analysis was performed in 34 participants to assess whether cirrhosis may affect entecavir metabolism. Participants were followed-up for a median (range) duration of 21 months (2–108). Results: Rates of virological response (negative viraemia by PCR for ≥2 consecutive determinations) after 12, 24 and 36 months were 91.7%, 97.5% and 93.7%, respectively. In the 84 patients who were treated for ≥12 months, presence of cirrhosis (OR 1.730, 95% CI 1.082, 2.766; P =0.022) and absence of hepatitis B e antigen (OR 0.479, 95% CI 0.273, 0.842; P =0.011) were independent predictors of earlier clearance of serum HBV DNA. There were no differences between the serum concentrations in the steady-state level of entecavir between patients with or without cirrhosis. No significant differences were detected between the average area under the curve in the means of the two groups ( P =0.55). Conclusions: Entecavir represents an excellent therapy in patients with HBV-related liver disease and particularly with cirrhosis where it showed a good profile of tolerability, higher efficacy and an earlier virological response.